Designing for Trust-Building Interactions in the Initiation of a Networked Improvement Community - Kallio, Julie M.; Halverson, Richard R. (Frontiers in Education, 2020)
Networked Improvement Community (NICs) are increasingly recognized as a social innovation for orchestrating sustained change in education. NICs are one type of a research-practice partnership that provides a model for researchers and educators to bring insights about what works locally to scale. A critical aspect of NIC success is the emergence of relational trust across the participant network. At initiation, therefore, NIC leaders must create the conditions for long-term development of relational trust, which can be operationalized to be the existence of reciprocated, help-based interactions. To understand how NIC leaders foster these reciprocated, help-based interactions, this paper leverages social network and qualitative data to explore how the core activities of a NIC might foster help-based interactions amongst participants. This paper is a case study of how social network and qualitative data analysis might be applied to the design and development of NICs, and social innovation more broadly. We explore the context of the Personalization in Practice - Networked Improvement Community, which brought together 21 educators from five schools around a common challenge. Our analysis highlights how collaborative design activities created the conditions for relational trust to emerge: sparking interactions around shared practices, creating situations for participants to ask for help, and encouraging reciprocated, help-based interactions. Our findings demonstrate how specific collaborative design activities can foster the kinds of trust-building networks necessary for NIC success. This paper presents an applied case of using analytic research methods for the design of social innovation. The triangulation of social network and qualitative data provided insight into the internal dynamics of the partnership and has implications for development measures of network health. We found that the social network data described that interaction changed, but did not indicate which activities led to these changes. This case contributes to emerging research on how to measure the effects Networked Improvement Communities on participants and their practices. We demonstrate, on a practical level, how social network and qualitative data might be used to generate network-level data for improvement, and we contribute theoretical insight into the way collaborative design creates the conditions for the long-term development of relational trust.